A COMPARATIVE STUDY OF EFFICACY, SAFETY, AND ONSET OF ACTION OF VILAZODONE WITH ESCITALOPRAM IN PATIENTS OF MAJOR DEPRESSIVE DISORDER AT TERTIARY CARE HOSPITAL - Ankushe, Rohini D; DESHMUKH, VINOD S; Chepure, Ashish H; Jaju, Jugalkishore B (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: To compare efficacy, safety, and onset of action of Vilazodone with Escitalopram in treatment of major depressive disorder (MDD). Methods: A prospective, randomized, active-controlled, and parallel–group comparative open label study was conducted among 92 patients of MDD attending psychiatry OPD of a tertiary care center. They were divided into control and experimental groups receiving Escitalopram and Vilazodone, respectively. Hamilton depression rating scale (HAM-D), Hamilton anxiety rating scale (HAM-A), Montgomery-Asberg depression rating scale (MADRS), clinical global impression improvement (CGI-I), and CGI-severity (CGI-S) scores were assessed at the end of 1st, 2nd, 4th, and 12th weeks in both the groups. Results: There was significant decrease in HAM-D, HAM-A, MADRS, CGI, and CGI-S scores in control as well as the experimental groups. Experimental group receiving Vilazodone showed significant decrease in the scores as compared to control group (p<0.001) at the end of 2nd and 4th week. Although the number of adverse effects were more in the Vilazodone group leading to higher score on UKU scale, the difference was not statistically significant. Conclusion: The present study showed clinical advantages of use of Vilazodone over Escitalopram with improvement in all the scores. Significant reduction in scores was seen as early as 1 week in Vilazodone group which justifies its early onset of action and superiority over selective serotonin reuptake inhibitors.